Integrated CO2 capture and utilisation: A promising step contributing to carbon neutrality - Liu, Guanying; Sun, Shuzhuang; Sun, Hongman; Zhang, Yu; Lv, Jiabao; Wang, Youhe; Zeng, Jingbin; Yan, Zifeng; Wu, Chunfei (Carbon Capture Science & Technology, 2023)
The release of CO2 into the atmosphere is problematic; however, it is an abundant, renewable, and inexpensive carbon resource. In the past, the environmental problems caused by excessive CO2 emissions, such as global warming and ocean acidification, have become increasingly severe. Carbon capture and utilisation (CCU) has drawn intensive interest due to its capacity to sequester CO2 and utilise it as a carbon source to produce high-value chemicals and fuels. However, state-of-the-art CCU exhibits poor economics and technological complexity due to extensive energy input, a multiple reactor configuration, and sorbent transfer between reactors for sorbent regeneration. Integrated CO2 capture and utilisation (ICCU) directly utilises CO2-containing exhaust gas and in situ upgrades them into valuable products in a highly intensified process, representing a more direct and promising path for CO2 emission control. A series of high-performance dual functional materials (DFMs) composed of catalytic and adsorbent sites have succeeded in various ICCU applications. In this account, we first briefly introduced the research background of ICCU technology and the motivation for developing various ICCU applications. Furthermore, we conducted a detailed description of ICCU technology from three aspects: ICCU-methanation, ICCU-dry reforming methane (DRM) and ICCU-reverse water gas shift reaction (RWGS). In particular, we have investigated the optimal adsorption and catalytic sites for specific reaction characteristics and have solved the problem of temperature matching between the adsorption and catalytic sites. In addition, The mechanism underlying ICCU technology has been explored, and the effect of interfering components on catalytic performance in real plant flue gases for future applications has also been analysed. Significantly, the catalyst stability was effectively improved by investigating the causes of catalyst deactivation. Finally, although the technology of in situ CO2 capture and conversion is still in its preliminary stages, we can see that current research results already indicate promising prospects. In-situ capture and conversion of CO2 into high-value-added chemical feedstock will be a very attractive application for reducing greenhouse gases in the atmosphere and recycling carbon resources. We are also committed to promoting the industrialisation and large-scale production of ICCU technology. [Display omitted]